Convergence non-destructive evaluation system for the parts and materials. (May 2015) - Choi, S.-H.; Han, J.-H.; Kim, J.-Y.
Abstract : Ultrasound infrared thermography non-destructive analysis system for main shaft of offshore wind power generator is established. As preliminary study, optimal design of ultrasound excitation equipment and infrared thermography analysis for optimal design and external energy control is investigated. For the improved defect detection capability through higher energy penetration, optimal design for ultrasound transducer and excitation time (defect detection time) is determined. Impact of ultrasound incident angle and contact point of ultrasound horn is analysed. In addition, amplitude is controlled through controller for ultrasound excitation, and elastic wave from ultrasonic energy will be injected to test unit in a short amount of time using lock-in wave mode. Periodic injection causes heat generation in defect area, and time for preventing significant temperature increase and cooling time is also controllable. Using the specially designed and fabricated jig for ultrasound infrared thermography, optimal design for ultrasound equipment can be achieved.